ERAS protocol in the treatment of older people - Prylińska, Monika; Husejko, Jakub; Skierkowska, Natalia; Bieniek, Daria; Rupniak, Iga; Wycech, Alicja; Gaborek, Patryk; Osiak, Joanna; Rozmarynowicz, Ewa; Gajos, Małgorzata; Topka, Weronika; Kudanowska, Agnieszka; et al. (Journal of Education, Health and Sport, 2019)
Background: The guidelines for elderly recommend nutritional assessment in order to prevent malnutrition and make fast recovery after operation and mobilization possible. The ERAS protocol shortens the length of hospital stay and reduces the complication rate.Material and methods: A systematic review of published literature has been done for the factors reported to predict outcomes of enhanced recovery after surgery (ERAS) among the elderly patients.Results: The improvement of treatment effects must be supported by a multidisciplinary medical team involved in the whole process with holistic approach which reduces time of regeneration and cost of health careConclusions: ERAS protocol implementation is highly beneficial for operated patients due to faster recovery and strong psychological support by providing information concerning the perioperative period and reducing stress caused by the surgery. However, must be supported by a team of professional medical staff.